(untitled) (Journal of the Asiatic Society of Bangladesh, Humanities, 2025)
The heritage inscription from Khan Jahan Ali in the city of Khalifatabad is a countenance of indigenous techniques with imperial Delhi, creating a unique identity. Some stunning architectural engravings are revealed here with its own exemplary expression. As well as some of the intangible heritages created and grew up around the built heritages of Bagerhat and became a source of some cultural, social and religious inspiration. Although distinct in nature, such traditional patterns form powerful imaginative, global domains through the interaction of meanings and values in spiritual, touristic, scholarly and civic contexts. The purpose of this research is to explore the intangible components and define long-term possessions of the religious built environment on a socio-cultural lifeline. Historical discoveries of remarkable cultural immaterial of present Bagerhat city are indexed. Bagerhat is a UNESCO World Heritage Site. Behind this recognition, as much as its physical and architectural appearance has come to the fore, its underlying embodied soul has not been revealed holistically. In this study an attempt has been made to discover the inner essence of this tradition through physical inspection. Moreover, various books, journals, and papers have been used as a basis. Unstructured interviews and discussions were also held with some recitalists because their ideas could not be rejected if cultural compassions were to be taken. The intangible cultural elements, if properly identified, will contribute to the appropriate live preservation of heritage sites and provide evidence of cultural continuity and fluidity during the past. The outcomes of the study provide some basis for better understanding of the history, culture, rituals, values and later preservation, restoration or conservation of intangible cultural heritages of Khalifatabad. JASBH, Vol. 70(1), June 2025, pp. 123-142